Seed germination and seedling emergence of synedrella (Synedrella nodiflora) in a tropical environment - Chauhan, Bhagirath S.; Johnson, David E. (Cambridge University Press, 2009)
Synedrella is a tropical annual plant species of the family Asteraceae that is widely distributed in many crops in nearly 50 countries. Experiments were conducted to determine the influence of various environmental factors on seed germination and seedling emergence of synedrella. Germination response was greater at 30/20 C and 35/25 C than at 25/15 C fluctuating day/night temperatures. Light stimulated germination; however, a small proportion of after-ripened seeds germinated in the dark. Seedling emergence was greatest (96%) for seeds placed on the soil surface but declined with increased seed burial depth. No seedlings emerged from a depth of 4 cm. Seedling emergence and seedling dry matter declined with the addition of crop residue to the soil surface; however, higher quantities of residue than those normally found in low-yield systems were required to result in substantial reductions in emergence. Seed germination was tolerant of moderate salt concentrations (40 to 100 mM sodium chloride) and a broad range of pH (4 to 10) but was sensitive to low osmotic potentials (< −0.8 MPa). The information gained from this study could help predict the invasion potential of this species and could lead to improved management strategies.